A Quadruplex RT-qPCR for the Detection of African Swine Fever Virus, Classical Swine Fever Virus, Porcine Reproductive and Respiratory Syndrome Virus, and Porcine Pseudorabies Virus - Zhuo Feng; Kaichuang Shi; Yanwen Yin; Yuwen Shi; Shuping Feng; Feng Long; Zuzhang Wei; Hongbin Si (Animals)
African swine fever virus (ASFV), classical swine fever virus (CSFV), porcine reproductive and respiratory syndrome virus (PRRSV), and porcine pseudorabies virus (PRV) induce similar clinical signs in infected pigs, including hyperthermia, anorexia, hemorrhage, respiratory distress, neurological symptoms, and/or abortions in pregnant sows. The differential diagnosis of these diseases relies on laboratory examinations. In this study, a quadruplex RT-qPCR was established using four pairs of specific primers and probes aimed at the B646L (p72) gene of ASFV, the 5′ untranslated region (5′UTR) of CSFV, the ORF6 gene of PRRSV, and the gB gene of PRV for the detection and differentiation of ASFV, CSFV, PRRSV, and PRV. The assay exhibited great sensitivity with limits of detection (LODs) of 134.585, 139.831, 147.076, and 142.331 copies/reaction for ASFV, CSFV, PRRSV, and PRV, respectively. The assay exclusively identified ASFV, CSFV, PRRSV, and PRV, yielding negative results for the other control swine viruses used in this study. The intra-assay and inter-assay coefficients of variation (CVs) were not higher than 1.12%, indicating good reproducibility of the assay. The quadruplex RT-qPCR assay was used to analyze 3116 clinical tissue samples from pigs in Guangxi province, China, from April 2023 to September 2024. ASFV, CSFV, PRRSV, and PRV had positivity rates of 10.84% (338/3116), 0.80% (25/3116), 14.92% (465/3116), and 1.38% (43/3116), respectively, demonstrating a coincidence rate of ≥99.45% with the previously described RT-qPCR assays, which were also used to test these same samples. The established assay was rapid, sensitive, and accurate in detecting and differentiating ASFV, CSFV, PRRSV, and PRV.